1992
DOI: 10.1002/jctb.280530212
|View full text |Cite
|
Sign up to set email alerts
|

Study of the poisoning of γ‐Al2O3 by alkali metals addition

Abstract: The effect of alkali metal addition to alumina on the acid characteristics and on the isopropanol dehydration capacity was analyzed. It was found that the incidence on the catalytic and acid properties of the alkali metal doped alumina depended on the ionic radii of the added element. Thus, K produces a higher poisoning of the acid function than Na and Li. Catalytic results can be interpreted in terms of a modification of the acid sites distribution by the alkali metal addition, the stronger acid sites being m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…When the sodium content exceeds 1.0%, almost no NH 3 desorption at higher temperature appears. This result clearly indicates that sodium can neutralize the strong acidic sites of the catalysts effectively, which is consistent with the results of prior research [29,30].…”
Section: Catalysts Characterizationsupporting
confidence: 81%
“…When the sodium content exceeds 1.0%, almost no NH 3 desorption at higher temperature appears. This result clearly indicates that sodium can neutralize the strong acidic sites of the catalysts effectively, which is consistent with the results of prior research [29,30].…”
Section: Catalysts Characterizationsupporting
confidence: 81%
“…Moreover, the selectivity to di-isopropylether displays an analogous behaviour since it decreases with the increase of the Na content, such as also shows. Taking into account that the ether formation would require strong acid sites [7], the results obtained in the isopropanol dehydration would be in agreement with the higher poisoning capacity of Na on the stronger acid sites of the alumina. Fig.…”
Section: Characterization Of the Acid And Metallic Phasesupporting
confidence: 72%
“…Jiratová reported a selective poisoning of the support when alumina is doped with Na ions. García Cortéz et al [7], by using ammonia thermodesorption, found that Li, Na and K ions poison the acid sites of alumina. Moreover, these authors reported that the strong acid sites are poisoned by the addition of small quantities of alkali metal ions.…”
Section: Introductionmentioning
confidence: 98%
“…5 In this case, water in the form of H 2 O -and ОН -can be removed from the same active sites that are present in the starting samples, which explains the TSE curves similar in shape (see Fig. 3) recorded upon isopropyl alcohol decomposition in the adsorption layer.…”
Section: Resultsmentioning
confidence: 90%
“…ESR spectra of anthraquinone adsorbed on the surface of the γ Al 2 O 3 and Li + /Al 2 O 3 samples(1)(2)(3)(4)(5). The spectra were recorded at 20 °С.…”
mentioning
confidence: 99%